Terrorist rehabilitation and community engagement in Malaysia and Southeast Asia - Mohd Mizan Aslam; Gunaratna, Rohan 1961- (Routledge studies in the politics of disorder and instability, 2020)
The contributors to this book analyse the different approaches and modes of terrorist rehabilitation that have been attempted by Malaysia, and other countries in Southeast Asia. With an emphasis on the particular contexts within which they operate, this book examines the factors that determine the relative successes and failure of a wide range of community initiatives in integrating terrorists back into society. These initiatives include using methods based on social psychology, religion, and entrepreneurship to develop a comprehensive approach to rehabilitating and deradicalizing terrorists in Malaysia as well as Singapore, Indonesia and the Philippines. As such it makes an important contribution to the global policy debate, coloured by the unique characteristics of the South East Asia region. A valuable resource for researchers and policymakers seeking constructive ways to counter violent extremism.